AYURVEDIC MANAGEMENT OF KITIBHA KUSHTA (PLAQUE PSORIASIS) WITH VIRECHANA AND SIRAVEDHA CHIKITSA - A CASE STUDY - Dr Vijay Baburao Mane; Raj, Raj Achhelal Yadav; Dr Iram Ansari (Ayurline: International Journal of Research in Indian Medicine, 2025)
Psoriasis is a non-infectious, inflammatory disease of the skin, characterised by well defined erythmatous plaques with large, adherent, silvery scales. The main abnormility in Psoriasis is increased epidermal proliferation, due to excess proliferation of cells in the basal layer and a shorter cell cycle time. The transit time of keratinocytes through the epidermis is shorterened and epidermal turnover time falls from 28 to 5 or 6 days[1] In ayurveda skin disorders have been described in Kushta Adhyaay, which further divides skin diseases in two broad categories i.e mahakushta and kshudra kushta. This paper highlights a case study of Kitibh kushta treated with ayurvedic shamana chikitsa and shodhana chikitsa (Virechana and Siravedha)